Elliptic Curves, Hilbert Modular Forms and Galois Deformations - Berger, Laurent (Birkhäuser, 2013)
Part I: Galois Deformations -- On p-adic Galois Representations -- Deformations of Galois Representations -- Part II: Hilbert Modular Forms -- Arithmetic Aspects of Hilbert Modular Forms and Varieties -- Explicit Methods for Hilbert Modular Forms -- Part III: Elliptic Curves -- Notes on the Parity Conjecture.
Keywords: Modulform; Galois-Theorie; Zahlentheorie; Algebraische Geometrie; Algebra; Elliptische Kurve